Case report and literature review: Malignant adenomyoepithelioma after breast augmentation - Hu, Longqing; Qian, Bei; Yan, Zhecheng; Bing, Kaijian; Mei, Li; Qu, Xincai (Frontiers in Surgery, 2022)
Background Breast malignant adenomyoepithelioma (MAME) after breast augmentation has never been reported. Case summary We reported a case of a 55-year-old woman who was diagnosed with breast MAME 16 years after breast augmentation. Breast augmentation was performed on the patient with two 200 ml round textured prostheses in the subpectoral plane through axillary incisions in 2004. However, a breast ultrasound in 2020 revealed a suspicious malignant lump in the right breast, which was finally confirmed as MAME by pathology. Skin-sparing modified radical mastectomy and immediate breast reconstruction with expander implantation were performed. Subsequently, the patient received three cycles of chemotherapy with the regimen of anthracycline and cyclophosphamide. In the following nearly 2 years of follow-up, no tumor recurrence and metastasis were found, and the overall treatment was satisfactory for the patient. Conclusion Here, we present a unique case in which a patient was diagnosed with breast MAME after breast augmentation. Skin-sparing modified radical mastectomy and immediate breast reconstruction with expander implantation are feasible approaches that yield at least short-term oncological safety and acceptable aesthetic results. However, whether there is a potential relationship between MAME and breast implants remains to be further explored. Meanwhile, due to the rarity of breast MAME, more authoritative strategies considering both oncological safety and aesthetics to seek better long-term therapeutic effects are needed.